Phenylalanine and tyrosine levels are rate-limiting factors in production of health promoting metabolites in Vitis vinifera cv. Gamay Red cell suspension - Manela, Neta; Oliva, Moran; Ovadia, Rinat; Sikron-Persi, Noga; Ayenew, Biruk; Fait, Aaron; Galili, Gad; Perl, Avichai; Weiss, David; Oren-Shamir, Michal (Frontiers in Plant Science, 2015)
Environmental stresses such as high light intensity and temperature cause induction of the shikimate pathway, aromatic amino acids (AAA) pathways, and of pathways downstream from AAAs. The induction leads to production of specialized metabolites that protect the cells from oxidative damage. The regulation of the diverse AAA derived pathways is still not well understood. To gain insight on that regulation, we increased AAA production in red grape Vitis vinifera cv. Gamay Red cell suspension, without inducing external stress on the cells, and characterized the metabolic effect of this induction. Increased AAA production was achieved by expressing a feedback-insensitive bacterial form of 3-deoxy- D-arabino-heptulosonate 7-phosphate synthase enzyme (AroG*) of the shikimate pathway under a constitutive promoter. The presence of AroG* protein led to elevated levels of primary metabolites in the shikimate and AAA pathways including phenylalanine and tyrosine, and to a dramatic increase in phenylpropanoids. The AroG* transformed lines accumulated up to 20 and 150 fold higher levels of resveratrol and dihydroquercetin, respectively. Quercetin, formed from dihydroquercetin, and resveratrol, are health promoting metabolites that are induced due to environmental stresses. Testing the expression level of key genes along the stilbenoids, benzenoids and phenylpropanoid pathways showed that transcription was not affected by AroG*. This suggests that concentrations of AAAs, and of phenylalanine in particular, are rate-limiting in production of these metabolites. In contrast, increased phenylalanine production did not lead to elevated concentrations of anthocyanins, even though they are also phenylpropanoid metabolites. This suggests a control mechanism of this pathway that is independent of AAA concentration. Interestingly, total anthocyanin concentrations were slightly lower in AroG* cells, and the relative frequencies of the different anthocyanins changed as well.